Sugar transport and water relations of Agaricus bisporus - Molloy, Shannon (Cranfield University, 2004)
The A. bisporus fruit body can develop from a 0.5 cm primordium to a 7 cm fruit body within 6 days and it is this rapid growth and expansion which was investigated. The mycelium and fruit body extract water and solutes from the compost and casing soil. Water and solute translocation is thought to occur by osmotically derived pressure driven mass flow whereby the accumulation of the polyol mannitol in the fruit body lowers the water potential and allows for an influx of water which increases the turgor pressure and creates a turgor gradient thus driving water and solutes into the mycelium. This work investigated the mechanism of water and sugar translocation through the mycelium and into the developing sporophore and the factors which affect this translocation path. The effect of different water stresses (osmotic and matric) on mycelial growth, osmotic, turgor and water potential and the accumulation of endogenous sugars and polyols when grown on two different media: a defined malt extract and compost derived was investigated. The concentration of various sugars and polyols was measured in the following sporophore tissue: cap, gills, skin and upper and lower stipe. A sugar transporter gene SUT1 which had previously been identified in A. bisporus was fully characterised. The mycelium was most sensitive to changes in matric than osmotic potential on malt extract agar (MEA) medium and there was no mycelial growth below -0.98 MPa on matrically modified medium but the mycelium continued to grow at water stresses of -1.48 and -2.48 MPa on osmotically modified MEA medium. However on compost derived medium less difference was found between osmotic and matric stresses. The following sugars: glucose and trehalose and the polyols: mannitol, glycerol and erythritol were quantified in the mycelium and mannitol was found to be the dominant polyol which increased with increasing water stress in the mycelium. However in mycelium grown on matrically modified compost media at -0.48 and -0.98 MPa the mannitol levels didn’t increase with increasing water stress and this was reflected by the mycelium having a lower internal water potential than the external medium indicating that the mycelial tolerance to matric stresses is linked to the components of the compost as no such tolerance was found on MEA medium. Mannitol was the main polyol detected in all the sporophore tissues but there were no significant differences between the stages of sporophore development indicating that there was no change in the levels of mannitol. Previous reports by Hammond and Nichols (1976) and Wannet et al. (2000) have shown that the level of mannitol increased during sporophore development but the difference could be attributed to the casing soil which is now wetter and therefore the sporophore is not under increasing water stress and can extract water without having to constantly adjust its polyol concentration. The SUT1 protein had a predicted molecular weight of 61.2 kDa and according to topology predictions had 12 transmembrane domains and a number of highly conserved regions which place it in the sugar transporter family of the major facilitator superfamily. The level of SUT1 transcript increased during sporophore development and there were higher but equal levels of SUT1 transcript in the upper and lower stipe compared to the cap, gills and skin tissue (indicated by Northern analysis). However no SUT1 transcript could be detected in the mycelium supporting stage 2 and 4 sporophore development indicating that it is possibly involved in translocation in the fruit body but not in the mycelium. The detection of the SUT1 protein by Westerns was attempted using an antibody raised to the SUT1 C-terminal region. However the extraction and solubilisation of the membrane bound SUT1 protein proved very difficult and was not successfully detected by Westerns.